Self-Rated Mental Stress and Exercise Training Response in Healthy Subjects - Ruuska, Pirita S.; Hautala, Arto J.; Kiviniemi, Antti M.; Mäkikallio, Timo H.; Tulppo, Mikko P. (Frontiers in Physiology, 2012)
Purpose: Individual responses to aerobic training vary from almost none to a 40 % increase in aerobic fitness in healthy subjects. We hypothesized that the baseline self-rated mental stress may influence to the training response. Methods: The study population included 44 healthy sedentary subjects (22 women) and 14 controls. The laboratory controlled training period was 2 weeks, including 5 sessions a week at an intensity of 75 % of the maximum heart rate (HR) for 40 min/session. Self-rated mental stress was assessed by inquiry prior to the training period from 1 (low psychological resources and a lot of stressors in my life) to 10 (high psychological resources and no stressors in my life), respectively. Results: Mean peak oxygen uptake (Vo2peak) increased from 34±7 to 37±7 ml•kg-1•min-1 in training group (p<0.001) and did not change in control group (from 36±6 to 36±6 ml•kg-1•min-1). Among the training group, the self-rated stress at the baseline condition correlated with the change in fitness after training intervention, e.g. with the change in maximal power (r=0.45, p=0.002, W/kg) and with the change in Vo2peak (r=0.32, p=0.039, ml•kg-1•min-1). The self-rated stress at the baseline correlated with the change in fitness in both female and male e.g. r=0.44, p=0.039 and r=0.43, p=0.045 for W/kg in female and male, respectively. Conclusion: As a novel finding the baseline self-rated mental stress is associated with the individual training response among healthy females and males after highly controlled aerobic training intervention. The changes in fitness were very low or absent in the subjects who experience their psychological resources low and a lot of stressors in their life at the beginning of aerobic training intervention.